¿La teoría del Arco Pleisto qué? - Argentinas, Aves; Prado, Darién; Mogni , Virginia; Oakley, Luis; Maturo, Hernán; Galetti, Luciano (Revista Aves Argentinas, 2016)
Accedé al artículo ingresando a la revista (hacé click sobre la portada y/o el número).